(untitled) (aSSIST Business Review, 2026)
This study examines how a politically under-resourced candidate successfully overcame structural disadvantages through strategic design in the 2002 South Korean presidential election. Focusing on the campaign of Roh Moo-hyun, the paper analyzes how a strategic model—rather than tactical improvisation—was employed to transform the candidate’s status as a political outsider into a competitive advantage. The study introduces the "OPEN Strategy Model" (Online, Participation, Engagement, Network) and interprets its structural composition and implementation mechanism through the SER-M strategy framework and the Weight-Sequence (W-S) execution model. Rather than relying on quantitative hypothesis testing, this research adopts a proposition-based analytical approach, identifying three core propositions and examining how the strategy influenced voter behavior and electoral outcomes through a sequential mechanism. The OPEN strategy differed from traditional, resource-intensive campaign models by emphasizing digital communication, emotional resonance, citizen-led engagement, and horizontal network mobilization. Through qualitative case analysis, this paper argues that the OPEN model not only mitigated the limitations of political resources but also redefined them as opportunities for strategic leverage. The findings provide structural insights into how such a model can be applied and generalized to future political campaigns led by resource-constrained candidates.